Pengaruh Easy of Use, Sales Promotion, dan Trust Terhadap Minat Beli Ulang pada Live Streaming Shopee - Trisabela Aryanti; Syahrul Alim (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
This study aims to determine the influence of ease of use, sales promotion, and trust on repurchase intention in Shopee live streaming. The population in this study is all Shopee application users who make repeat purchases on Shopee live streaming, with a sample size of 100 respondents. The data collection method used is non-probability sampling with purposive sampling technique. The data analysis in this study uses quantitative methods with the help of SmartPLS ver. 4.0 software. The results of the study indicate that ease of use has a positive and significant effect on repurchase intention, sales promotion has a positive and significant effect on repurchase intention, and trust also has a positive and significant effect on repurchase intention in Shopee live streaming.